2010
DOI: 10.1002/aqc.1148
|View full text |Cite
|
Sign up to set email alerts
|

How to protect a diverse, poorly known, inaccessible fauna: identification and protection of source and sink habitats in the epikarst

Abstract: ABSTRACT1. Aquatic subterranean species are often geographically and numerically scarce. Many of these species are denizens of epikarst, the uppermost zone of karst with semi-isolated solutional openings and channels, and are only known from drip pools in caves where they accumulate as a result of animals dripping out of the epikarst.2. The question of whether these pool communities adequately reflected the epikarst community was addressed by directly collecting animals from drips in a continuous collecting de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 22 publications
1
30
0
Order By: Relevance
“…Since drips are fed directly from the epikarst, the fauna of drips is the result of dislodgement of organisms which consequently drift in the water column, and the composition of the animals in drips should be an approximation of the fauna of epikarst. However, different species can have different susceptibility or propensity to enter the water column (based on their size, body shape, locomotory ability, developmental phase) and, as a consequence, the fauna of drip pools is an incomplete sample of the fauna of drips (Pipan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since drips are fed directly from the epikarst, the fauna of drips is the result of dislodgement of organisms which consequently drift in the water column, and the composition of the animals in drips should be an approximation of the fauna of epikarst. However, different species can have different susceptibility or propensity to enter the water column (based on their size, body shape, locomotory ability, developmental phase) and, as a consequence, the fauna of drip pools is an incomplete sample of the fauna of drips (Pipan et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…This mosaic of microhabitats hosts a variety of taxa, including a rich array of small crustaceans Culver 2005, Pipan 2005), resulting in a diversity often rivalling the diversity of the rest of the karstic aquifer (Pipan andBrancelj 2004, Brancelj and. The epikarst has been recently shown to host a high local richness and biodiversity in several European countries, Italy included (Pipan and Culver 2007a, Dole-Olivier et al 2009, Galassi et al 2009, Michel et al 2009), and to be often a source of new and endemic species (Pipan et al 2010). More specifically, the epikarst is a perched aquifer, "…partially saturated with water and capable of delaying or storing and locally rerouting vertical infiltration to the deeper regional phreatic zone of the underlying karst aquifer" (Jones et al 2004); it is typically 3 to 10 m deep (Williams, 2008), but it can extend to a depth of up to 30 m (Klimchouk 2000).…”
Section: Introductionmentioning
confidence: 99%
“…However, it is difficult to exactly establish microhabitat associations for subterranean species. Frequent floods and other events can perturb species and obfuscate their place of origin [31]. A recent study of functional morphological diversity in North American subterranean amphipods found no conclusive connection between morphology of species and their habitat [27].…”
Section: Resultsmentioning
confidence: 99%
“…brucei, Bryocamptus dacicus, and Bryocamptus sp.-was separated by Faunal differences between drips and drip pools Most data on epikarst fauna comes from collections of individuals from drip pools. Drip pools are not necessarily passive collectors of the epikarst fauna in drips, and Pipan et al (2010) specifically addressed the question of whether the fauna of drip pools reflected the drip community. Overall, the frequency of stygobionts was 1.5 times higher in drips than in pools, and the frequency of stygobionts that were epikarst specialists was three times higher in drips compared with pools.…”
Section: Peştera Doboş 3 Total 11mentioning
confidence: 99%
“…The frequency of immature individuals, suggestive of reproduction at the site, was also higher in drips than in pools, with the exception of one artificially enlarged pool in Škocjanske jame. Pipan et al (2010) suggest that there is increased juvenile mortality in pools and reduced reproduction, indicating that pools are not "source populations", i.e., populations that are selfsustaining in the absence of migrants (Pulliam, 1988).…”
Section: Peştera Doboş 3 Total 11mentioning
confidence: 99%